Symposium 7: Constructing ethnicity and identity in the online classroom: Linguistic practices and ritual text acts - Macfadyen, Leah P. (Proceedings of the International Conference on Networked Learning, 2008)
In any new learning environment, diverse learners are expected to engage intellectually with peers, course materials and instructors, through argumentation, discussion and critical reflection on ideas. This expectation presupposes, however, a wealth of background understanding: shared assumptions, shared concepts, shared understanding of methods of argument. If learners do not arrive with a common cultural (and intellectual) heritage, they must negotiate or co-construct a new learning culture in which the ‘rules of engagement’ are understood and shared, before fruitful intellectual engagement can begin. In this paper I argue that development of a new group culture requires that individuals can first effectively enact their particular identities. For any learning community to develop, for the construction of a learning culture to begin, learners must first be able to enact their authentic and differing identities in the learning space. Which strategies of self-presentation and identity construction are available to learners when the new learning environment is virtual? Cyberspace (and, in particular, virtual learning environments), remains primarily a ’written world’ (Feenberg, 1989), one in which bodily markers of identity such as physical attributes and vocal accent, are often invisible and bodily participation in gesture and ritual is impossible. The body has, to a large extent, been banned (Zurawski, 2000) from the ‘discursive and rhetorical discursive spaces’ of the Internet (Nakamura, 2002), and yet an individual’s authenticity – a term that in English connotes ‘truth’, ‘accuracy of (self)representation’ and ‘trustworthiness’ – is commonly assumed to be guaranteed by physical presence (Feenberg, 1989) and the evidence of the senses. Concerns therefore persist about the Internet as a problematic site for meaningful learner interaction and negotiation of learning cultures that can support ‘engaged collaborative discourse’. Can there be learning cultures that do not depend for their existence on physical presence? If so, how can we best characterize their nature and development? I will argue here that, as in face-to-face classrooms, learners in text-based virtual learning environments begin the process of co-constructing a virtual learning culture by performing and sharing their unique virtual identities, and that one of the key strategies that individuals and newly forming virtual communities make use of in this process is ritual. To investigate how learners enact their identities in a virtual classroom, I examined web-based student communications in an international online undergraduate course, Perspectives on Global Citizenship, in which participating students represent a great diversity of national, cultural and disciplinary backgrounds. I present, here, some of this data, with a focus on ‘ritual text acts’ that participants seem to perform. I draw attention to the ways participants not only ritually perform their affiliations with established national, ethnic or ‘racial’ groups through the use of stylized language, but also how they then ritually challenge these essentialized models of identity. In particular, I explore apparent ritual performances of new hybrid global identities, and moments of ritual resistance to expected learner identities or practices. Based on these findings, I argue that in virtual learning environments, learners transfer and transform ‘first life’ rituals of identity formation and community building into forms that exemplify (new) cultural values and practices. Learners perform themselves through a range of ritual text-as-speech acts that do not simply describe pre-existing identity but also construct it. Transferring elements of real life rituals (for example the use of coded language) to the virtual space, they ritually restate details of their ethnic or national membership (or non-membership) in order to clarify or trouble the identity they possess through a range of other group affiliations, attesting their individual identities in relation to others. Together, these practices help learners establish authentic virtual identities that permit the establishment of a new learning community with a shared learning culture.